Association of Horizontal Silo Pad Type, Elevation and Core Depth With Indicators of Silo Ramp Hygiene, Forage Quality, and Digestibility - W. E. Brown; N. M Bello; M. J. Brouk (Kansas Agricultural Experiment Station Research Reports, 2020)
Horizontal silo piles without walls are constructed using packing equipment to adequately pack the forage for air exclusion. During packing, the equipment uses a ramp of forage to access the top of the pile, potentially introducing soil into the forage when the base of the silo is made of soil. Soil contains microorganisms which may cause malfermentation and pose health risks to livestock. The objective of this study was to assess the association of horizontal silo pad type, elevation, and core depth with indicators related to silage hygiene and nutrient quality. We hypothesized that ash and mineral content, microbiological profile, and fermentation profile in silos with soil pads would be indicative of soil contamination, and that measures of potential contamination would be lesser at higher elevations within the silo. Eleven horizontal silos on 7 farms were sampled in a split-split-plot design, with silo pad type as the whole plot factor, elevation on the ramp as the split-plot factor, and core depth as the split-split-plot factor; data were analyzed using mixed models to appropriately recognize experimental units for each factor. Regardless of core depth and elevation, silage pH was increased in concrete pads relative to soil pads. Also, for soil pads, phosphorus (P) was increased in samples of the outer core depth compared to inner core depths. Further, on both pad types, iron (Fe) content was greater at lower vs. medium elevations, but there was no evidence of difference for peak Fe content compared with the other elevations. On soil pads, outer layers had decreased 120- and 240-hour neutral detergent fiber (NDF) and 7-hour starch digestibility compared with inner cores regardless of elevation. The outer segments also had increased pH and decreased density compared with inner core depths, regardless of pad type or elevation. Further, independent of pad type or elevation, outer layers increased NDF, acid detergent fiber (ADF), lignin, ash, and minerals, but decreased crude protein (CP) compared with inner core depths. Additionally, compared with inner layers, outer layers had decreased NDF and starch digestibility, and increased undigestible NDF regardless of pad type or elevation. Overall, changes in Fe and P may be indicative of soil contamination on soil pads. Furthermore, the decreased quality of forage in the outer layers of the silo reinforces the importance of an anaerobic environment for the adequate preservation of silage.
Keywords: silage hygiene; silage contamination; silage degradation